CHALLENGES AND UTILIZING RESULTS EFFECTIVELY IN INTERNA THE TIONAL EVALUATION ADDRESSING PROCESSES - Sayfiddinova Ruxsora; Ahmedov Azimjon (TADQIQOTLAR.UZ, 2024)
The rapid and profound transformations occurring in our country in recent years necessitate a re-evaluation of all aspects of human life, viewed through the lens of globalization and integration, demanding new perspectives, understandings, and approaches. Globalization and integration processes are currently evident in every sector worldwide. Education, in particular, has become a priority area of state policy, with reforms underway to develop education based on innovative ideas. Societal and life changes demand a new innovative approach to the education system, accelerating the integration of education, science, and production. Consequently, the application of new innovations to the educational process has become a pressing issue.